2015
DOI: 10.1002/2014jc010320
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glacial drainage water on the CO2 system and ocean acidification state in an Arctic tidewater‐glacier fjord during two contrasting years

Abstract: In order to investigate the effect of glacial water on the CO 2 system in the fjord, we studied the variability of the total alkalinity (A T ), total dissolved inorganic carbon (C T ), dissolved inorganic nutrients, oxygen isotopic ratio (d 18 O), and freshwater fractions from the glacier front to the outer Tempelfjorden on Spitsbergen in winter 2012 (January, March, and April) and 2013 (April) and summer/fall 2013 (September).The two contrasting years clearly showed that the influence of freshwater, mixing, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
123
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(177 citation statements)
references
References 48 publications
13
123
3
Order By: Relevance
“…Kongsfjorden has a similar physical marine environment as another west Spitsbergen fjord, Tempelfjorden, with the inflow of TAW and influence of glacial freshwater drainage from tide-water glaciers. In Tempelfjorden, Fransson et al (2015) observed higher A T in the freshwater source water in a warmer year (2012) with larger freshwater content in the fjord (1142 lmol kg -1 ) compared with a colder winter (2013) when there was less freshwater content (526 lmol kg -1 ). Higher A T in freshwater is likely due to the supply of carbonate-rich glacial drainage water originating from calcite and dolomite minerals from the bedrock.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…Kongsfjorden has a similar physical marine environment as another west Spitsbergen fjord, Tempelfjorden, with the inflow of TAW and influence of glacial freshwater drainage from tide-water glaciers. In Tempelfjorden, Fransson et al (2015) observed higher A T in the freshwater source water in a warmer year (2012) with larger freshwater content in the fjord (1142 lmol kg -1 ) compared with a colder winter (2013) when there was less freshwater content (526 lmol kg -1 ). Higher A T in freshwater is likely due to the supply of carbonate-rich glacial drainage water originating from calcite and dolomite minerals from the bedrock.…”
Section: Discussionmentioning
confidence: 86%
“…The high X a in summer was likely an effect of biological CO 2 uptake. Previous studies have shown that the increased X, because of biological CO 2 uptake during photosynthesis, counteracts decreases in X due to freshwater supply (Chierici and Fransson 2009;Chierici et al 2011;Fransson et al 2015). To investigate the net effect of these two processes, we inspected the influence of freshening due to addition of glacial water on the OA state at the glacier front, where the freshening signal is most pronounced.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations